2001
DOI: 10.1021/la010610s
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of a Cationic Amphiphile Monolayer by Polyanions in the Subphase and Computational Modeling of the Complex at the Air−Water Interface

Abstract: Intermolecular interactions across the air−water interface are the basis for a variety of investigations on monolayers and adsorption phenomena at the interface. We present a systematic study of the influence of different anions in the aqueous subphase on the formation and stabilization of a monolayer of the cationic amphiphile N-octadecyl-4-dimethylaminopyridinium. Some polyanions such as polystyrenesulfonate in the subphase are shown to impart strong stability to the monolayer. The monolayer stabilization th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…3d), deconvolution unambiguously indicates that any peak assigned in the range 320±400 nm attributable to the dimer has negligible intensity; the finite absorption around 350 nm arises from the broad polyelectrolyte absorption centered near 260 nm. [14] A Figure 4 demonstrate these trends clearly. The growth of the dimer accompanying the monomer disappearance and the isosbestic points ( Fig.…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…3d), deconvolution unambiguously indicates that any peak assigned in the range 320±400 nm attributable to the dimer has negligible intensity; the finite absorption around 350 nm arises from the broad polyelectrolyte absorption centered near 260 nm. [14] A Figure 4 demonstrate these trends clearly. The growth of the dimer accompanying the monomer disappearance and the isosbestic points ( Fig.…”
mentioning
confidence: 71%
“…[10] We have shown that polyanions introduced in the subphase can dramatically improve the stability of a pyridinium-based Langmuir film. [14] It was also demonstrated that the SHG from LB films of the cationic hemicyanine dye is enhanced when the films are fabricated with polyanions in the subphase, due to deaggregation of the NLO-phores without dilution. [12,13] In this work, the polyelectrolyte methodology is shown to be an effective strategy to arrest SHG degradation in the hemicyanine LB film as well.…”
mentioning
confidence: 99%
“…In this context we have examined the utility of the polyelectrolyte based approach we have previously developed for the stabilization of otherwise unstable ionic amphiphiles at the air-water interface. 14 We have observed that N-n-octadecyl-4-[2-(4-dimethylaminophenyl)ethenyl]pyridinium bromide (ODEP + Br -) ( Fig. 1) is effectively deaggregated in its Langmuir films at the air-water interface, by the introduction of polyelectrolytes such as sodium poly(4-styrenesulfonate) ((Na + ) n PSS n-) in the aqueous subphase.…”
Section: Introductionmentioning
confidence: 99%
“…Amphiphiles with ionic headgroups are best served by this approach since efficient binding can be achieved through electrostatic complexation with polyelectrolytes such as poly(styrene sulfonate) (PSS), carboxymethyl cellulose (CMC), deoxyribonucleic acid (DNA) and poly(vinyl sulfate) (PVS). The utility of this approach was first de- monstrated using a pyridinium based amphiphile; monolayers of this amphiphile at the air-water interface was found to collapse completely under compression, but to form a stable film when templated using PSS as well as some of its copolymers (Sharma et al 2001).…”
Section: Polyelectrolyte Templated Langmuir-blodgett Films: Second Hamentioning
confidence: 99%
“…A large number of variations on these basic themes have been developed over the years. We have shown that polyelectrolyte templating is a particularly versatile and efficient technique to overcome a number of fundamental limitations of the LB method, such as Langmuir film instability at the airwater interface (Sharma et al 2001) and molecular aggregation in the ultrathin films (Chandra et al 2003). Molecular nanostructures have been demonstrated to possess novel and unique properties and hence are suitable for several applications.…”
Section: Introductionmentioning
confidence: 99%